Methodological aspects of universities’ R&D comercialization in Ukraine in the context of the Quаdruplе Hеlіx Model - Nataliya I. Kholiavko; Tetyana Shestakovska (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2018)
The necessity of the formation and development of the mechanism of commercialization of the researches results of HEIs in Ukraine has been substantiated. The present state of the process of commercialization of the researches results of HEIs in Ukraine has been analyzed. The problems and strategic guidelines for improving the mechanism of commercialization of the researches results of HEIs in Ukraine have been identified. The components of the mechanism of commercialization of the researches results of the HEIs in Ukraine in the context of implementation of the